AmrZ Regulates Swarming Motility Through Cyclic di-GMP-Dependent Motility Inhibition and Controlling Pel Polysaccharide Production in Pseudomonas aeruginosa PA14 - Hou, Lingli; Debru, Alexander; Chen, Qianqian; Bao, Qiyu; Li, Kewei (Frontiers in Microbiology, 2019)
Swarming is a surface-associated motile behavior that plays an important role in the rapid spread, colonization and subsequent establishment of bacterial communities. In Pseudomonas aeruginosa, swarming is dependent upon a functional flagella and aided by the production of biosurfactants. AmrZ, a conserved transcription factor across pseudomonads, has been shown to be a global regulator of multiple genes important for virulence and ecological fitness. In this study, we expand this concept of global control to swarming motility by showing that deletion of amrZ results in a severe defect in swarming, while multicopy expression of this gene stimulates swarming of P. aeruginosa. Mechanistic studies showed that the swarming defect of an amrZ mutant does not involve changes of biosurfactant production but is associated with flagellar malfunction. The ∆amrZ mutant exhibits increased levels of the second messenger cyclic-di-GMP (c-di-GMP) compared to the wild-type strain, under swarming conditions. We found that the diguanylate cyclase GcbA was the main contributor to the increased accumulation of c-di-GMP observed in the ∆amrZ mutant and was a strong inhibitor of flagellar-dependent motility. Our results revealed that the GcbA-dependent inhibition of motility required the presence of two c-di-GMP receptors containing a PilZ domain: FlgZ and PA14_56180. Furthermore, the ∆amrZ mutant exhibits enhanced production of Pel polysaccharide. Epistasis analysis revealed that GcbA and the Pel polysaccharide act independently to limit swarming in ΔamrZ. Our results support a role for AmrZ in controlling swarming motility, yet another social behavior besides biofilm formation that is crucial for the ability of P. aeruginosa to colonize a variety of surfaces. The central role of AmrZ in controlling these behaviors makes it a good target for the development of treatments directed to combat P. aeruginosa infections.